Recent changes in channel morphology of a highly engineered alluvial river – the Lower Mississippi River. (4th March 2018) - Joshi, Sanjeev; Jun, Xu Y.
Abstract: Changes in channel morphology provide relevant insights into sediment transport and deposition in alluvial river systems. This study assessed three to four decades of morphological changes at seven locations along a 327-km reach of the Lower Mississippi River (LMR) to better understand channel adjustment processes of this large alluvial river. The assessment included analysis of three cross-sectional areas at each location during the period 1992–2013, as well as analysis of the changes in river stage and maximum surface slopes under four flow conditions over the last three to four decades . We found that the first 20–25 km LMR reach below its diversion to the Atchafalaya River and the reach from 80 to 140 km experienced significant riverbed aggradation, while the reach in between (i.e. from 20 to 80 km) experienced riverbed degradation. The lower 187-km reach (i.e. from 140 to 327 km) showed negligible sediment trapping. These findings may have relevant implications for management of river sediment diversions along the LMR and other large alluvial rivers in the world.